Glutamine deprivation induces metabolic adaptations associated with beta cell dysfunction and exacerbate lipotoxicity - Carlessi, Rodrigo; Rowlands, Jordan; Ellison, Gaewyn; Helena de Oliveira Alves, Heloisa; Newsholme, Philip; Mamotte, Cyril (Molecular and cellular endocrinology, 2019)
Studies have reported that plasma glutamine is reduced in type 2 diabetes (T2D) patients. Glutamine supplementation improves glycaemic control, however the mechanisms are unclear. Here, we evaluated in vitro the pancreatic beta cell bioenergetic and insulin secretory responses to various levels of glutamine availability, or treatment in the presence of an inhibitor of intracellular glutamine metabolism. The impact of glutamine deprivation to the pathological events induced by the saturated fatty acid palmitate was also investigated. Glutamine deprivation induced a reduction in mitochondrial respiration and increase in glucose uptake and utilization. This phenotype was accompanied by impairment in beta cell function, as demonstrated by diminished insulin production and secretion, and activation of the unfolded protein response pathway. Palmitate led to insulin secretory dysfunction, loss of viability and apoptosis. Importantly, glutamine deprivation significantly exacerbated these phenotypes, suggesting that low glutamine levels could participate in the process of beta cell dysfunction in T2D. •Glutamine availability determines metabolic flux in BRIN-BD11 clonal beta cells.•Decrease in glutamine induces glycolysis and suppresses oxidative phosphorylation.•Glutamine deprivation triggers the UPR and leads to insulin secretory dysfunction.•Lipotoxicity is exacerbated in the absence of glutamine.